Intergender Relations in «Saturnalia», by Rima de Vallbona - Alonso Chacón, Paula (2026)
An analysis is presented of intergender relations in the short story “Saturnalia” (1993), by Rima de Vallbona. The term androcentrism and its link with hegemonic male identity, the individualistic ideology of modernity and male superiority over women are taken as a reference to examine the phenomena of alienation, projection and reification. The study reveals that both protagonists were objectified: he, because androcentrism and technology alienated him psychologically to the point of turning him into a computerized artifact; she, because she suffers the projection of male objectification and domestic slavery that annulled her as a woman.